Ultimate bias. Memorabilia, K-pop and fandom identities - Paula Guerra; Sofia Sousa (Cidades, Comunidades e Território)
This article puts forward a sustained approach in the perception of the processes of construction of – individual and collective – meanings and identities in relation to the musical (sub)genre K-pop. Thus, contrary to the logic that emphasizes the loss of relevance of the CD, we tried to demonstrate that – as an object of memorabilia and musical consumption – it remains alive within the K-pop culture. In fact, not only the CD, but also other memorabilia items that emphasize the creation of visual and identity narratives, in the sense that they are seen as a means to establish, maintain and cement a relationship with the idol. Thus, in parallel to the fact that K-pop, as a musical genre, has a global character, it also highlights individual, regional and local aspects, mainly due to the variety of products that are produced, following a personalisation logic at the same time as we are facing a mass selling process. Thus, through the use of a qualitative methodology (Guerra, 2021; Pink, 2020), we intend to analyze the memorabilia items of seven Portuguese K-pop fans, in order to perceive the processes of identity creation, but also to denote the symbologies and meanings that are built around the items.